A Developmental Perspective to Attention-Deficit Hyperactivity Disorder (ADHD) in Children - Emmanuel Afolabi Olusegun (East European Journal of Psycholinguistics, 2016)
The debate about diagnoses and treatment of attention deficit hyperactive disorder (ADHD) in children continue to range on between the developmental and biological perspectives. While there is increasing evidence that support the biological susceptibility of the disorder, a number of researches also emphasized the significant effect of environment on the syndrome. This study used developmental perspectives to evaluate and bring together various bio-psychosocial factors that impact on children diagnosed with ADHD. The study explored and integrated the existing and advancing study on ADHD to a more refined pattern that embraced developmental perspectives. The study also discussed how the linkage in childhood ADHD fits within the developmental psychopathology perspective. The study revealed that ADHD as a developmental disorder is influenced by prenatal, biological and psychosocial environmental risk factors, and suggested that better understanding of genomic susceptibilities, family environment and parental characteristics would transform the pathway for development of ADHD in children. References American Psychiatric Association.(2000). Diagnostic and StatisticalManual of Mental Disorders. 4th ed. Washington, DC: American Psychiatric Association. American Psychiatric Association.(2013). Diagnostic and StatisticalManual of Mental Disorders.5th ed. Washington, DC: American Psychiatric Association. Arnsten, A.F, (2007). Catecholamine and second messenger influenceson prefrontal cortical networks of “representational knowledge”:a rational bridge between genetics and the symptoms of mental illness. Cerebral Cortex, 17, i6–i15. Arnsten, A.F, & Pliszka, S.R. (2011). Catecholamine influences on prefrontalcortical function: relevance to treatment of attentiondeficit/hyperactivity disorder and related disorders. Pharmacology, Biochemistry and Behavior, 99, 211–216. Atladóttir H.O, Parner E.T, & Schendel D. (2007). Variation in incidence of neurodevelopmental disorders with season of birth. Epidemiology, 18, 240–245. Barkley, R. A. (2006). Attention deficit/hyperactivity disorder: A handbook for diagnosis and treatment (3rd ed.). New York: Guilford Baumeister A.A, Hawkins M.F (2001). Incoherence of neuroimaging studies of attention deficit/ hyperactivity disorder. Clinical Neuropharmacology, 24, 2–10. Berger I. (2011). Diagnosis of attention deficit hyperactivity disorder: much ado about something. Israeli Medical Association Journal, 13, 571–574. Berger, A., Posner, M. I. (2000). Pathologies of brain attentionalnetworks. Neuroscience and Biobehavioral Reviews, 24, 3–5. Biederman J, Faraone S.V, Keenan K, Knee D, &Tsuang M.T (1990): Familygenetic and psychosocial risk factors in DSM-III attention deficit disorder. Journal of American Academy of Child and Adolescent Psychiatry, 29, 526 –533. Biederman J, Faraone SV, Keenan K, Tsuang MT (1991b): Evidence of familialassociation between attention deficit disorder and major affective disorders. Archives of General Psychiatry, 48, 633–642. Biederman, J, Faraone, S.V, Keenan K, Benjamin, J, Krifcher, B. &Moore C. et al (1992). Further evidence for family-genetic risk factors in attention deficit hyperactivity disorder. Patterns of comorbidity in probands and relativesin psychiatrically and pediatrically referred samples. Archives of General Psychiatry, 49, 728 –738. Biederman, J., Milberger, S., Faraone, S. V., Kiely, K., Guite, J.,Mick, E., Ablon, S., Warburton, R., & Reed, E. (1995). Family environment risk factors for attention deficit hyperactivity disorder: A test of Rutter’s indicators of adversity. Archives of General Psychiatry, 52, 464–470. Biederman, J., Faraone, S.V., Mick, E., Spencer,T.,Wilens,T., Kiely,K., Guite, J., Ablon, J. S., Reed, E., & Warburton, R. (1995). High risk for attention deficit hyperactivity disorder among children of parents with childhood onset of the disorder: A pilot study. Journal of American Psychiatry, 152, 431–435. Biederman J, Faraone S.V, Monuteaux M, Spencer T, Wilens T, Bober M, et al (2004). Gender effects of attention deficit hyperactivity disorder inadults, revisited. Biological Psychiatry, 55, 692–700. Brookes, K.,Mill, J.,&Guindalini,C., et al (2006). Acommon haplotype of the dopamine transporter geneassociated with attention-deficit/hyperactivity disorderand interacting withmaternal use of alcohol duringpregnancy. Archives of General Psychiatry, 63, 74–81. Brophy, K., Hawi, Z., Kirley, A., Fitzgerald, M., & Gill, M. (2002). Synaptosomalassociated protein 25 (SNAP-25) and attention deficit hyperactivity disorder (ADHD): Evidence of linkage and association in the Irish population. Molecular Psychiatry, 7 , 913– 917 Campbell, S. B. (2000). Attention-Deficit/Hyperactivity Disorder: A developmental view. In: Handbook of Developmental Psychopathology. (pp. 383–401). A. J. Sameroff, M. Lewis, & S. Miller (Eds.). New York: Kluwer Academic/Plenum. Carlson, E. A., Jacobvitz, D., & Sroufe, L. A. (1995). A developmental investigation of inattentiveness and hyperactivity. Child Development, 66, 37–54. Childress, A.C, Berry, S.A (2012). Pharmacotherapy of attention-deficit hyperactivity disorder in adolescents. Drugs, 72, 309–325. Cortese, S (2012). The neurobiology and genetics of attention-deficit/hyperactivity disorder (ADHD): what every clinician shouldknow. European Journal of Paediatric Neurology, 16, 422–433. Dopheide, J.A (2005). ASHP therapeutic position statement on theappropriate use of medications in the treatment of attention deficit/hyperactivity disorder in paediatric patients. American Journal of Health System Pharmacy, 62, 1502– 1509. Coghill, D., Nigg, J., Rothenberger, A., Sonuga-Barke, E., & Tannock, R. (2005). Wither causal models in the neuroscience of ADHD? Developmental Science, 8, 105–114. Cummings, E. M., Davies, P., & Campbell, S. B. (2000). Developmental Psychopathology and Family Process: Research, Theory, and Clinical Implications. New York: Guilford. Faraone, S. V., Perlis, R. H., Doyle, A. E., Smoller, J. W., Goralnick, J. J., Holmgren, M. A., et al. (2005). Molecular genetics of attention-defi cit/hyperactivity disorder. Biological Psychiatry, 57 , 1313–1323. Faraone, S, Biederman, J, Krifcher Lehman, B, Keenan, K, Norman, D, Seidman, L. et al. (1993). Evidence for the independent familial transmission of attentiondeficit hyperactivity disorder and learning disabilities: Results froma family genetic study. American Journal of Psychiatry, 150, 891– 895. Faraone, S. V, Tsuang, M. T. (1995). Methods in psychiatric genetics. In: Textbook in Psychiatric Epidemiology, Tohen, M, Tsuang, M., Zahner, G. (Eds). (pp. 81–134). New York: John Wiley& Sons. Faraone, S. V. & Biederman, J. (1998). Neurobiology of attentiondeficit hyperactivity disorder. Biological Psychiatry, 44, 951–958. Faraone S.V, Biederman J, &MonuteauxM.C. (2001a). Attention deficit hyperactivity disorder with bipolar disorder in girls: Further evidence for a familial subtype? Journal of Affect Disorders, 64, 19 –26. Haraone S.V, Doyle A.E (2001): The nature and heritability of attentiondeficit/hyperactivity disorder. Child and Adolescent Psychiatric Clinics of North America, 10, 299 –316, viii–ix. Faraone, S.V., & Biederman, J. (2000). Nature, nuture, and attentiondeficit hyperactivity disorder. Developmental Review, 20, 568–581. Faraone S.V, Perlis R.H, Doyle A.E, Smoller J.W, Goralnick J, &Holmgren M.A, et al. (2005). Molecular genetics of attention deficit hyperactivity disorder. Biological Psychiatry, 57, 1313–1323. Gray, J. A., Feldon, J., Rawlins, J. N. P., Hemsley, D. R., & Smith, A. D. (1991) The neuropsychology of schizophrenia. Behavioral and Brain Sciences, 14, 1–84. Gray, J. A. (1982). The neumpsychology of anxiety. New York: Oxford University Press. Halperin, J. M., & Healey, D. M. (2011). The infl uences of environmental enrichment, cognitive enhancement,and physical exercise on brain development: Can we alter the developmental trajectory of ADHD? Neuroscience and Biobehavioral Reviews, 35 , 621– 634. Hauschild K.M, Mouridsen S.E, & Nielsen S. (2005). Season of birth inDanish children with language disorder born in the 1958–1976 period. Neuropsychobiology; 51, 93–99. Hudziak J.J, Rudiger L.P, Neale M.C, Heath A.C, & Todd R.D (2000). A twin study of inattentive,aggressive, and anxious/depressed behaviors. Journal of the American Academy of Child and Adolescent Psychiatry, 39, 469 –476. Kahn, R. S., Khoury, J. & Nichols,W.C., et al (2003). Role of dopamine transporter genotype and maternal prenatal smoking in childhood hyperactive-impulsive,inattentive, and oppositional behaviors. Journal of Pediatrics, 143, 104–110. Kesner R.P, & Churchwell J.C (2011). An analysis of rat prefrontal cortexin mediating executive function. Neurobiology of Learning and Memory, 96, 417–431. Kuntsi, J.,& Stevenson, J. (2000). Hyperactivity in children:Afocuson genetic research and psychological theories. Clinical Child and Family Psychology Review, 3, 1–24. Langley, K., Rice, F., & van den Bree, M. B., et al (2005). Maternal smoking during pregnancy as an environmental risk factor for attention deficit hyperactivity disorder behaviour. A Review. Minerva Pediatrica, 57, 359–371. Manshadi M, Lippmann S, O’Daniel R, & Blackman A (1983): Alcohol abuse and attention deficit disorder. Journal of Clinical Psychiatry, 44, 379 –380 Martin N, Scourfield J, McGuffin P (2002).Observer effects and heritability ofchildhood attention-deficit hyperactivity disorder symptoms. British Journal of Psychiatry, 80, 260 – 265. Neale, B. M., Medland, S. E., Ripke, S., Asherson, P., Franke, B., Lesch, K. P., et al. (2010). Meta-analysis of genome-wide association studies of attention-defi cit/ hyperactivity disorder. Journal of the American Academy of Child and Adolescent Psychiatry, 49 , 884–897. Nigg J, Nikolas M, & Burt S. A(2010). Measured gene-by-environment interaction in relation to attention-deficit/hyperactivity disorder. Journal of the American Academy of Child and Adolescent Psychiatry, 49, 863–73. Oades, R. D., Lasky-Su, J., Christiansen, H., Faraone, S.V., Sonuga-Barke, E. J., Banaschewski, T., et al. (2008). The influence of serotonin- and other genes onimpulsive behavioral aggression and cognitive impulsivity in children with attentiondeficit/hyperactivity. A Developmental Perspective on ADHD disorder (ADHD): Findings from a family-based association test (FBAT) analysis. Behavioral and Brain Functions, 4, 4–48. Pastor P. N & Reuben C.A. (2008). Diagnosed attention deficit hyperactivity disorder and learning disability: United States, 2004–2006. Vital Health Statistics, 10, 1–14. Quay, H. C. (1988a). Attention deficit disorder and the behavioral inhibitionsystem: The relvance of the neuropsychological theory of Jeffrey A. Gray. In: Attention deficit disorder: Criteria, cognition, intervention (pp. 117–126). L. M. Bloomingdale & J. Sergeant (Eds.). NewYork: Pergamon. Quay, H. C. (1988b). The behavioral reward and inhibition systems inchildhood behavior disorder. In: Attentiondeficit disorder W; New research in treatment, psychopharnmcology, and attention (pp. 176–186). L. M. Bloomingdale (Ed.). NA: Pergamon. Quay, H. C. (1996, January). Gray’sbehavioral inhibition in ADHD:An update. Paper presented at the annual meeting of the InternationalSociety for Research in Child and Adolescent Psychopathology, Los Angeles, CA. Rader, R, McCauley L,& Callen, E.C. (2009). Current strategies in thediagnosis and treatment of childhood attention-deficit/hyperactivity disorder. American Family Physician, 79, 657–665. Robbins, T. W. (2003). Dopamine and cognition. Currpin Neurol,16, (2), S1–S2. Rutter, M, Cox, A, Tupling, C, Berger, M, &Yule, W. (1975). Attainment and adjustment in two geographical areas. 1—The prevalence of psychiatric disorders. British Journal of Psychiatry, 126, 493–509. Rutter, M., &Sroufe, L. A. (2000). Developmental psychopathology: Concepts and challenges. Development and Psychopathology, 12, 265–296. Sergeant, J. (2000). The cognitive-energetic model: An empiricalapproach to attentiondeficit hyperactivity disorder. Neuroscienceand Biobehavioral Reviews, 24, 7–12. Sherman D, McGue M, &Iacono W (1997). Twin concordance for attention deficit hyperactivity disorder: A comparison of teachers’ and mothers’reports. American Journal of Psychiatry, 154, 532–535. Sonuga-Barke, E. J., Auerbach, J., Campbell, S. B., Daley, D., & Thompson, M. (2005). Preschool varieties of hyperactive and dysregulated behaviour: Multiple pathways between risk and disorder. Developmental Science, 8 , 141–150. Sonuga-Barke, E. J., Bitsakou, P., & Thompson, M. (2010). Beyond the dual pathway model: Evidence for the dissociation of timing, inhibitory, and delayrelated impairments in attention-defi cit/hyperactivity disorder. Journal of the American Academy of Child and Adolescent Psychiatry, 49 , 345–355. Sonuga-Barke, E. J., & Halperin, J. (2010). Developmental phenotypes and causal pathways in attention deficit/hyperactivity disorder: Potential targets for early intervention? Journal of Child Psychology and Psychiatry, 51, 368–398. Sprich-Buckminster S, Biederman J, Milberger S, Faraone S, &Krifcher LehmanB (1993): Are perinatal complications relevant to the manifestation ofADD? Issues of comorbidity and familiality. Journal of American Academy of Child and Adolescent Psychiatry,32, 1032–1037 Swanson, J. M., Sunohara, G. A., Kennedy, J. L., Regino,R., Fineberg, E.,Wigal, T., Lerner, M.,Williams, L., LaHoste,G. J.,&Wigal, S. (1998). Association of the dopamine receptorD4 (DRD4) gene with a refined phenotype of attention deficithyperactivity disorder (ADHD): A family–based approach.Molecular Psychiatry, 3, 38–41. Taylor, E. (1999). Developmental neuropsychopathology of attentiondeficit and impulsiveness. Development and Psychopathology, 11, 607–628. Thapar, A.,O’Donovan,M., &Owen,M. J. (2005b). The genetics of attention deficit hyperactivity disorder. Human Molecular Genetics, 14, 275–282. Thapar, A., Langley, K.,O’Donovan,M. (2006). Refining the attention deficit hyperactivity disorderphenotype formolecular genetic studies. Molecular Psychiatry, 11, 714–720. Thapar A, Langley K, &Asherson P, (2007). Gene–environment interplay in attentiondeficit hyperactivity disorder and the importance of a developmental perspective. British Journal of Psychiatry 190, 1–3. Tochigi M, Okazaki Y, & Kato N, (2004). What causes seasonality of birth in schizophrenia? Neuroscience Res, 48, 1–11 Trent S & Davies W. (2012). The influence of sex-linked genetic mechanisms on attention and impulsivity. Biological Psychology, 89, 1–13. United States, 2003 and 2007 (2010). Increasing prevalence of parent-reported attentiondeficit/hyperactivity disorder among children, MMWR Morb Mortal Wekly Rep, 59, 1439– 43. Yehuda, R. (2000). Biology of posttraumatic stress disorder. Journal of Clinical Psychiatry, 61, 14–21. Zimmer, L (2009). Positron emission tomography neuroimagingfor a better understanding of the biology of ADHD. Neuropharmacology, 57, 601–607.